2010
DOI: 10.1002/anie.201003978
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Orbitals and Stress in Mechanochemistry

Abstract: The use of mechanical stress to guide molecular systems along specific reaction pathways has gained considerable interest recently. [1] This interest has been driven by sonication experiments, [2] which showed that the ring opening of benzocyclobutene (BCB) with polymeric substituents on the carbon atoms of the scissile bond can be selectively directed along competing pathways in violation of the Woodward-Hoffmann (WH) rules.[3] Specifically, the thermally allowed conrotatory pathway was followed if the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 19 publications
2
28
1
Order By: Relevance
“…Here Q is a vector of 3N-6 non-redundant internal coordinates of the molecule with Q(1) being the constrained molecular coordinate (note that the system of equations does not generally have a unique solution, that is, even a single conformer would have several geometries that would satisfy the system of equations). This strategy was used successfully [20][21][22]24 to calculate electronic energies of activation of cyclobutene ring-opening and analogous reactions in single ground and transition-state conformers of small molecules. This approach is particularly useful for MD simulations, but its current implementations remain too expensive for optimizations of thermodynamic states comprising dozens or hundreds of individual conformers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here Q is a vector of 3N-6 non-redundant internal coordinates of the molecule with Q(1) being the constrained molecular coordinate (note that the system of equations does not generally have a unique solution, that is, even a single conformer would have several geometries that would satisfy the system of equations). This strategy was used successfully [20][21][22]24 to calculate electronic energies of activation of cyclobutene ring-opening and analogous reactions in single ground and transition-state conformers of small molecules. This approach is particularly useful for MD simulations, but its current implementations remain too expensive for optimizations of thermodynamic states comprising dozens or hundreds of individual conformers.…”
Section: Methodsmentioning
confidence: 99%
“…Such force-dependent reactivity is thought to account for the behaviour of polymeric materials, melts and solutions under load, may be exploited to yield new stress-responsive, actuating and energy transducing materials [1][2][3][4][5][6][7][8][9][10] and may even allow characterization of transition states. 11 Considerable theoretical, 3,[12][13][14][15][16][17][18][19] computational 13,[20][21][22][23][24][25][26] and experimental [27][28][29][30][31][32][33][34] effort has been devoted to refine and validate a model of forcedependent kinetics for elementary (single-barrier) reactions. Yet many reactions proceed through one or more intermediates, that is, multiple activation barriers separate the reactant(s) from the product(s).…”
mentioning
confidence: 99%
“…102). Those include explicit incorporation of the force term into a PES 21,[106][107][108] (as in Eq. (8)), using constraints to simulate stretching, 1,[109][110][111] numerical integration of Eqs.…”
Section: A Which Bond Breaks First?mentioning
confidence: 99%
“…A large number of theoretical studies of chemical processes occurring under mechanochemical conditions have been reported to complement experimental efforts, help explain experimental outcomes, and provide new insights into the interplay between applied forces or stresses and chemical reactivity [29][30][31][32][33][34][35][36][37][38]. These studies have focused primarily on simulating molecular systems exposed to external forces by treating the system as though it moves on a force-modified potential energy surface that incorporates the work performed on a chemical system as it undergoes structural changes in the presence of an external force.…”
Section: Introductionmentioning
confidence: 99%